The Sun is Also a Star - Yoon, Nicola (UK, 2016)
This is a story of a girl, a boy, and the universe. NATASHA: I'm a girl who believes in science and facts. Not fate. Not destiny. Or dreams that will never come true. I'm definitely not the kind of girl who meets a cute boy on a crowded New York City street and falls in love with him. Not when my family is twelve hours away from being deported to Jamaica. Falling in love with him won't be my story. DANIEL: I've always been the good son, the good student, living up to my parents' high expectations. Never the poet. Or the dreamer. But when I see her, I forget about all that. Something about Natasha makes me think that fate has something much more extraordinary in store - for both of us. Did the Universe bring them together only to keep them apart?...
Keywords: Emotions & Feelings; Juvenile Fiction; Love & Romance